Diurnal Variations of Raindrop Size Distributions in the Tropical Region: Impact on Radar Measurement - Bamba, Bakary; Koffi, Augustin Kadjo; Soro, Séhéna; Kacou, Modeste; Zahiri, Éric-Pascal; Bamba, Ibrahima (European Journal of Applied Sciences, 2025)
The diurnal variations of raindrop size distributions (DSDs) observed in tropical Africa (Abidjan, Niamey, Boyélé, Dakar) and South America (Kourou) are analyzed to better understand this variability and its impact on radar measurements. The observed hourly diurnal DSDs display a distinct convex shape, characterized by a deficit of small drops and a pronounced variation across different daytime periods, particularly in African tropical sites. Local convection is suspected to be the cause of the broader afternoon spectra, whereas the narrower spectra observed in the evening and at night are likely due to organized convective systems, as suggested in the literature. The low diurnal variability of DSDs at the reference site of Kourou may be linked to the typically oceanic nature of precipitation in this region. The hourly diurnal Z=ARb relationships are not affected by the strong DSD variability at some sites, such as Abidjan. The introduction of a new empirical relationship ( – R proves to be relevant for quantitative precipitation estimation from radar or satellite remote sensing.